Position error-free control of magnetic domain-wall devices via spin-orbit torque modulation - Seong-Hyub Lee; Myeonghoe Kim; Hyun-Seok Whang; Yune-Seok Nam; Jung-Hyun Park; Kitae Kim; Minhwan Kim; Jiho Shin; Ji-Sung Yu; Jaesung Yoon; Chang, Jun-Young; Kim, Duck Ho; et al. (Nature Publishing Group, 2023)
Magnetic domain-wall devices such as racetrack memory and domain-wall shift registers facilitate massive data storage as hard disk drives with low power portability as flash memory devices. The key issue to be addressed is how perfectly the domain-wall motion can be controlled without deformation, as it can replace the mechanical motion of hard disk drives. However, such domain-wall motion in real media is subject to the stochasticity of thermal agitation with quenched disorders, resulting in severe deformations with pinning and tilting. To sort out the problem, we propose and demonstrate a new concept of domain-wall control with a position error-free scheme. The primary idea involves spatial modulation of the spin-orbit torque along nanotrack devices, where the boundary of modulation possesses broken inversion symmetry. In this work, by showing the unidirectional motion of domain wall with position-error free manner, we provide an important missing piece in magnetic domain-wall device development.